Land, water, and development : sustainable management of river basin systems - Newson, Malcolm David (Routledge, 1997)
This is a fully revised and expanded second edition of Malcolm Newson's acclaimed book. Exploring in greater depth the meaning of sustainability in river basin development this new edition:* highlights the rapid evolution of practical concepts since the Rio Earth Summit* features new illustrations and case studies from Australia, South Africa and Israel* makes the ecosystem model more explicit throughout* strengthens coverage of the linkages between land and water management.
Keywords: Watershed management.; Water resources development.; Sustainable development.; Bassins hydrographiques -- Gestion.; Ressources en eau -- Exploitation.; Développement durable.; water resources development.; sustainable development.; BUSINESS & ECONOMICS -- Real Estate -- General.; Sustainable development; Water resources development; Watershed management; Rivierbekkens.; Waterhuishouding.; Duurzame ontwikkeling.; Recursos naturais (utilizacao)